2022
DOI: 10.52547/wjps.11.1.148
|View full text |Cite
|
Sign up to set email alerts
|

An Early Experience of Microvascular Surgery in a Tertiary Cancer Centre in North East

Abstract: BACKGROUND Microvascular surgery is a highly technique sensitive and evolving speciality in reconstructive oncosurgery. There is a definite learning curve associated with it. In this case series, we describe our initial experience in microvascular surgery at a tertiary cancer centre in North East India. METHODS It is a retrospective observational case series done at a tertiary cancer centre in North East India from May 2018 to Jul 2018. The first ten cases of our free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The authors concluded that microvascular reconstruction is feasible in rural areas, with emphasis on team approach and protocol development 13 . A recent study from the Northeastern part of the country re‐emphasised the need for a trained team with adequate infrastructure to be able to deliver the best results 14 . A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high‐volume centres) 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors concluded that microvascular reconstruction is feasible in rural areas, with emphasis on team approach and protocol development 13 . A recent study from the Northeastern part of the country re‐emphasised the need for a trained team with adequate infrastructure to be able to deliver the best results 14 . A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high‐volume centres) 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…which need to be streamlined and scheduled appropriately so that there is no undue delay in caring for such patients given that free flaps take almost an entire day to complete. 10,13,14,22 Last but certainly not the least, a definite learning curve exists for microvascular surgeries and flap success and subsequent salvage rates improve with time. 23 This hastens the confidence of the entire team and one must not get bogged down by early failures during the learning curve, which has been evaluated to be at least 20 cases to | 1163 overcome the learning curve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations